2014
DOI: 10.1177/1534734614550311
|View full text |Cite
|
Sign up to set email alerts
|

Do Diabetic Foot Infections With Methicillin-ResistantStaphylococcus aureusDiffer From Those With Other Pathogens?

Abstract: There is controversy as to whether or not diabetic foot infections (DFIs) caused by methicillin-resistant Staphylococcus aureus (MRSA) are associated with worse outcomes than DFIs caused by other pathogens. To address this issue we performed a nonsystematic literature search of published articles in English language journals seeking studies reporting on the outcomes of DFIs related to their microbiology. We retrieved 48 articles published from 1999 to 2013 that described a total of 7771 cases of DFI. The overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 85 publications
2
46
1
1
Order By: Relevance
“…Secondly, we did not analyse the antibiotic agents that were used, or the role of specific pathogens. This is based on the lack of evidence that any specific systemic antibiotic regimen is significantly superior for treatment of DFI, regardless of the involved pathogens . Our study population and pathogens recovered were consistent with those reported in the literature .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Secondly, we did not analyse the antibiotic agents that were used, or the role of specific pathogens. This is based on the lack of evidence that any specific systemic antibiotic regimen is significantly superior for treatment of DFI, regardless of the involved pathogens . Our study population and pathogens recovered were consistent with those reported in the literature .…”
Section: Discussionsupporting
confidence: 84%
“…In total, 47 cases (10%) were complicated by bacteremia, 86 (18%) presented with soft tissue abscesses, and 139 (29%) with cellulitis. By notifying the three most prevalent microorganisms per DFI episode in our pathway, we detected 102 different microbiological combinations among the study population, with the four most frequently identified pathogens being Staphylococcus aureus (214 episodes, of which 53 were methicillin‐resistant), enterococci (n = 60), streptococci (n = 53) and Gram‐negative pathogens (n = 190, of which 35 Pseudomonas aeruginosa cases). Overall, 235 episodes (49%) were polymicrobial …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, no study has linked any particular organism to treatment failure, which is not surprising given the polymicrobial nature of most DFIs. For example, we and others have shown that infection with methicillin‐resistant S. aureus or obligate anaerobes has not been shown to be more deleterious than other pathogens. Additionally, wound cultures from our patients demonstrated 112 different microbiological constellations, making adequate retrospective analyses difficult.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, lower extremity amputation was performed during hospitalization in 35% and in another 19% of the 150 non‐amputated patients in the year after discharge; risk factors for amputation included severity of the infection and the presence of osteomyelitis. As in other studies , the presence of multidrug‐resistant pathogens [especially methicillin‐resistant S . aureus (MRSA)] was not associated with more severe infection or worse outcome.…”
Section: Introductionmentioning
confidence: 99%